Redefining Executive Power: Evolution of Presidential and Vice Presidential Roles in Indonesia’s Post-Amendment Con-stitutional System - M. Reza Saputra; Nabila Hilyatunisa (Badan Penerbit STIEPARI Press, 2025)
The Indonesian constitutional system underwent fundamental transformation following the four amendments to the 1945 Constitution between 1999 and 2002, fundamentally redefining the constitu-tional status of the President and Vice President within the framework of democratic transition. This study examines the comprehensive changes in executive authority, institutional design, and accountability mechanisms that emerged from Indonesia's gradualist approach to constitutional reform. Using normative legal research methodology through statute and conceptual approaches, this research analyzes primary legal materials including the amended 1945 Constitution, relevant legislation, and secondary materials com-prising scholarly journals and legal literature. The study employs a multi-dimensional analytical framework encompassing institutional, authority, accountability, and relational dimensions to assess the transfor-mation of executive power. Results demonstrate that the amendments successfully established direct popular elections for both offices, implemented two-term limitations, and created robust accountability mechanisms including judicial review by the Constitutional Court and enhanced legislative oversight. The constitutional reforms eliminated the previous concentration of virtually unlimited presidential power while strengthening the Vice President's role from a nominal position to a constitutionally empowered successor. The study concludes that Indonesia's gradualist constitutional reform approach successfully balanced democratic innovation with political stability, creating an effective separation of powers system with meaningful checks and balances, though challenges remain regarding democratic consolidation and institutional effectiveness in preventing authoritarian regression.